Інформаційне суспільство: соціологія та психологія блогерства - Міщенко, Марина Миколаївна (НТУ "ХПІ", 2018)
В роботі розглядається блогерство як пр ояв інформаційного суспільства. Аналізується блог як прояв особистості автора (блогера), його наративних та дискурсивних здібностей та журналістської етики.

The paper deals with the blogging as a manifestation of the information society. We consider the blog format as a manifestation of the author's narrative and discursive abilities, and of the journalistic ethics.
Information society: sociology and psychology of blogging
Keywords: блогерство; блогосфера; журналістика; blogging; blogosphere; journalism